Knowledge is power: A theory of information, income, and welfare spending - Jo Thori Lind; Dominic Rohner (University of Zurich, Department of Economics, 2011)
No voters cast their votes based on perfect information, but better educated and richer voters are on average better informed than others. We develop a model where the voting mistakes resulting from low political knowledge reduce the weight of poor voters, and cause parties to choose political platforms that are better aligned with the preferences of rich voters. In US election survey data, we find that income is more important in affecting voting behavior for more informed voters than for less informed voters, as predicted by the model. Further, in a panel of US states we find that when there is a strong correlation between income and political information, Congress representatives vote more conservatively, which is also in line with our theory.
Keywords: D31; D72; D82; H53; 330; Redistribution; Welfare Spending; Information; Income; Voting; Political Economics; Wahlverhalten; Informationsverhalten; Einkommen; Wissen; Neue politische Ökonomie; Politische Entscheidung; Öffentliche Sozialausgaben; USA